2020
DOI: 10.1002/jpen.1931
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition of Very Low‐Birth‐Weight Infants Fed Fortified Human Milk: A Pilot Study

Abstract: Background: Although donor milk is increasingly fed to preterm infants, the resultant quality of growth and body composition is unknown. The aim of this pilot study was to describe the body composition of very low-birth-weight infants fed human milk in the neonatal intensive care unit and explore the association between the proportion of donor human milk intake and fat-free and fat mass deposition. Methods: Body composition of 30 preterm infants fed maternal and donor human milk was measured by air displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In a recent study of 30 neonates, an increased intake of donor milk was associated with higher body fat percentage but did not have an impact on fat-free mass ( 28 ) . In this study, McNelis et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of 30 neonates, an increased intake of donor milk was associated with higher body fat percentage but did not have an impact on fat-free mass ( 28 ) . In this study, McNelis et.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, McNelis et. al, fortified the infant’s milk with a bovine based product and were unable to maintain a consistent caloric density of donor milk ( 28 ) . This approach differs from the one used in our study design.…”
Section: Discussionmentioning
confidence: 99%
“…Collected data included a retrospective convenience sample from three hospitals where care is provided by CCHMC Perinatal Institute physicians in 2013–2019: CHCMC, a 76‐bed level IV referral unit; the University of Cincinnati Hospital, a 50‐bed level III inborn unit; and Good Samaritan Hospital, a 60‐bed level III unit 18 . All centers use the same feeding protocol (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Collected data included a retrospective convenience sample from three hospitals where care is provided by CCHMC Perinatal Institute physicians in 2013-2019: CHCMC, a 76-bed level IV referral unit; the University of Cincinnati Hospital, a 50-bed level III inborn unit; and Good Samaritan Hospital, a 60-bed level III unit. 18 All centers use the same feeding protocol (Figure S1). Customized PN is started on the first day of life with a goal glucose infusion rate of 4-8 mg/kg/min; amino acids (TrophAmine) at 2.5 g/kg/day, which was advanced to 3.5 g/kg/day; and Intralipid (Fresenius Kabi/Baxter) at 1 g/kg/day, which was advanced to 3 g/kg/day.…”
Section: Cchmc-cincinnati Ohiomentioning
confidence: 99%
“…have demonstrated that infants fed fortified DHM have impaired short-term growth outcomes compared to infants fed fortified MOM (17,(19)(20)(21)(22)(23).…”
Section: Accepted Manuscriptmentioning
confidence: 99%